2019
DOI: 10.1039/c8cc07332e
|View full text |Cite
|
Sign up to set email alerts
|

SnS hollow nanofibers as anode materials for sodium-ion batteries with high capacity and ultra-long cycling stability

Abstract: In this study, a novel anode material of SnS hollow nanofibers (SnS HNFs) was rationally synthesized by a facile process and demonstrated to be a promising anode candidate for sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…According to XRD patterns, the milling time of 1 hour was found to be sufficient to obtain crystalline SnS phase and this phase can be still obtained when the milling time goes up to 20 hours. The 2θ angles and related main peaks are attributed to orthorhombic SnS phase 20,21 . The crystallite size was calculated by using Debye‐Scherrer Equation ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to XRD patterns, the milling time of 1 hour was found to be sufficient to obtain crystalline SnS phase and this phase can be still obtained when the milling time goes up to 20 hours. The 2θ angles and related main peaks are attributed to orthorhombic SnS phase 20,21 . The crystallite size was calculated by using Debye‐Scherrer Equation ().…”
Section: Resultsmentioning
confidence: 99%
“…The 2θ angles and related main peaks are attributed to orthorhombic SnS phase. 20,21 The crystallite size was calculated by using Debye-Scherrer Equation (1). The full width half of the maximum was evaluated using the peaks (011), (111), and (400) seen at 2θ of 30.5, 31.6, and 32.1, respectively.…”
Section: Electrochemical Testsmentioning
confidence: 99%
“…[ 281 ] Moreover, while the structure can adjust the volume change, its large specific surface area and electrochemical interface region can efficiently promote Na + insertion/extraction. Jia et al [ 268 ] fabricated highly porous SnS hollow nanofibers (SnS HNFs), which provided sufficient interior void space to buffer the volume expansion. The SnS HNF anode delivered an average capacity of 615 mA h g −1 at 0.1 A g −1 after 50 cycles (Figure 12d) and exhibited a high reversible capacity of 645 mA h g −1 at 0.1 A g −1 after 100 cycles.…”
Section: Applicationsmentioning
confidence: 99%
“…(d) is adapted with permission. [ 268 ] Copyright 2019, The Royal Society of Chemistry. (e) is adapted with permission.…”
Section: Applicationsmentioning
confidence: 99%
“…1,31 It has been shown that the hightemperature phase transition from the Pnma to phases alters the sample density and leads to enhanced phonon scattering, further lowering the thermal conductivity. [32][33][34] The indirect band gap also decreases through the phase transition, from 1.09 eV to 0.42 eV in SnS and from 0.61 to 0.39 eV in SnSe. 33,34 Finally, a recent study on SnSe revealed that the rocksalt phase has an even lower lattice thermal conductivity than the orthorhombic phase, suggesting rocksalt SnSe is also a potential high-performance thermoelectric.…”
Section: Introductionmentioning
confidence: 98%